Estimating the Effects of Recent Disability Reforms in The Netherlands - Jan-Maarten van Sonsbeek; Raymond Gradus (Tinbergen Institute, 2011)
In the 1980s and 1990s, disability benefit rates in the Netherlands were among the highest in the world. However, since the beginning of this century the number of disability cases has dropped remarkably due to some very successful policy reforms. An administrative dataset of Dutch disability benefit recipients from 1999 until 2010 has been used for analyzing the immediate effects on disability inflow and outflow of the recent policy measures. Three measures introduced between 1998 and 2004 have had a large effect reducing the inflow into the disability scheme by over 40 percentage points. The new disability scheme introduced in 2006 adds another reduction of over 20 percentage points. Effects differ substantially over demographic groups and sectors of economic activities. Furthermore, it is shown that the effects of re-examinations of the disability stock are substantial in the short run but may be overcompensated in the long run by adverse effects.
urn:NBN:nl:ui:31-1871/38529
Keywords: C15; H55; J26; 330; disability; policy reform